The Effect of Discovery Learning Model and Learning Style on Students' Interpersonal Intelligence in Social Studies Subjects - Hariyanti, Neneng Koes; Sabariah, Sabariah; Rahayu, Endah Yulia (Universitas Negeri Malang, 2024)
The purpose of this study was to determine the results of the test: The Influence Between the Discovery Learning Model and Visual, Auditory and Kinesthetic Learning Styles on Students' Interpersonal Intelligence in Social Studies. This experimental research and the subjects in this study were VII grade students of public schools in the city of Surabaya consisting of two classes, namely the Experimental class and the control class. The hypothesis of this study was tested using the ANOVA statistical test. Based on the results of the hypothesis testing and discussion, it can be concluded: There is a difference in the influence of the use of the Discovery Learning Model and the lecture method on Interpersonal Intelligence, There is a difference in the influence of different Learning Styles on Interpersonal Intelligence in Social Studies Class subjects, students with a tendency to use the Discovery Learning Model are visual and audio learning styles, while students with a tendency to use the lecture method are audio learning styles, and There is an interaction effect between the Discovery Learning Model and different Learning Styles on Interpersonal Intelligence, in this case different Learning styles as moderator variables strongly support a strong relationship between the independent variable and the dependent variable. The effect of using the Discovery Learning Model with different Learning Styles can improve students' Interpersonal Intelligence Abstrak Tujuan dari penelitian ini untuk mengetahui hasil pengujian: Pengaruh Antara Model Discovery Learning dan Gaya Belajar visual, auditori dan kinestetik Terhadap Kecerdasan Interpersonal Siswa pada mata pelajaran IPS. Penelitian yang bersifat eksperimen dan Subjek dalam penelitian ini adalah siswa Kelas VII sekolah negeri di kota Surabaya yang terdiri dua kelas yaitu kelas Eksprimen dan kelas kontrol. Hipotesis penelitian ini diuji menggunakan uji statistika ANOVA. Berdasarkan hasil pengujian hipotesis dan pembahasan maka dapat disimpulkan Terdapat perbedaan pengaruh penggunaan Model Discovery Learning dan metode ceramah terhadap Kecerdasan Interpersonal, Terdapat perbedaan pengaruh Gaya Belajar yang berbeda terhadap Kecerdasan Interpersonal pada mata pelajaran IPS Kelas, siswa dengan memiliki kecenderungan gaya belajar yang menggunakan Model Discovery Learning yaitu gaya belajar visual dan audio, sedangkan siswa dengan memiliki kecenderungan gaya belajar yang menggunakan metode ceramah adalah gaya belajar audio, dan Terdapat pengaruh interaksi antara Model Discovery Learning dan Gaya Belajar yang berbeda terhadap Kecerdasan Interpersonal, dalam hal ini gaya Belajar yang berbeda sebagai variabel moderator sangat mendukung hubungan yang kuat antara variabel bebas dan variabel terikatnya. Pengaruh penggunaan Model Discovery Learning dengan Gaya Belajar yang berbeda dapat meningkatkan Kecerdasan Interpersonal siswa